Lineage, Adoption, and Legal Dualism: A Case Study of the Inclusion of Adopted Children in Family Cards in Marihat Butar Village, Simalungun - Khoirunnisa, Ade; M. Yunus, Fakhrurrazi; Achyar, Gamal (Jurnal Mediasas: Media Ilmu Syari'ah dan Ahwal Al-Syakhsiyyah, 2026)
This research is motivated by the practice of altering the lineage of adopted children on the Family Card (Kartu Keluarga) in Marihat Butar Village without a court decree. This practice creates a problem in the form of a discrepancy between administrative facts and the provisions of positive law and Islamic law, which has not been extensively analyzed integratively from both legal perspectives. The objective of the research is to analyze the juridical consequences of this non-procedural lineage alteration, specifically its impact on population administration status and the civil rights of the child from the perspective of Islamic law. The method used is qualitative with a normative legal theory approach, collecting primary data through in-depth interviews with 5 adoptive couples, which were then analyzed descriptively-analytically. Results and discussion indicate that this practice creates legal dualism. In Islamic law, it results in the severance of legitimate lineage, inheritance rights, and mahram relations with the biological parents. Meanwhile, in positive law, this action creates inconsistency between population documents and biological facts, potentially causing issues regarding the child's civil legal status and public services. The implication of these findings reveals the urgency for socialization and strict law enforcement regarding legitimate child adoption procedures. There is also a need to integrate population administration databases with court rulings to prevent similar deviations in the future. [Penelitian ini dilatarbelakangi oleh praktik pengubahan nasab anak angkat dalam Kartu Keluarga (KK) di Desa Marihat Butar tanpa melalui penetapan pengadilan. Praktik ini menciptakan masalah berupa kesenjangan antara fakta administratif dengan ketentuan hukum positif dan hukum Islam, yang belum banyak dianalisis secara integratif dari kedua perspektif hukum tersebut. Tujuan penelitian adalah menganalisis konsekuensi yuridis dari pengubahan nasab secara tidak prosedural tersebut, khususnya dampaknya terhadap status administrasi kependudukan dan hak-hak keperdataan anak dalam perspektif hukum Islam. Metode yang digunakan adalah kualitatif dengan pendekatan teori hukum normatif, mengumpulkan data primer melalui wawancara mendalam terhadap 5 pasangan orang tua angkat, yang kemudian dianalisis secara deskriptif-analitis. Hasil dan pembahasan menunjukkan bahwa praktik ini menimbulkan dualisme hukum. Dalam hukum Islam, praktik ini mengakibatkan terputusnya hubungan nasab sah, hak waris, dan hubungan mahram dengan orang tua kandung. Sementara dalam hukum positif, tindakan ini menciptakan inkonsistensi antara dokumen kependudukan dan fakta biologis, berpotensi menimbulkan masalah dalam status keperdataan anak dan pelayanan publik. Implikasi dari temuan ini mengungkap urgensi sosialisasi dan penegakan hukum yang tegas mengenai prosedur pengangkatan anak yang sah. Diperlukan juga integrasi database administrasi kependudukan dengan putusan pengadilan agar dapat mencegah penyimpangan serupa di masa depan.]